Analisis Kinerja Keuangan dan Keputusan Strategis Dalam Perusahaan Energi Terbarukan - Fitriana, Siwi; Syaradifa, Annisya Fisca; Wahyudi, Muhamad (Universitas Labuhanbatu, 2024)
The renewable energy industry has become a strategic sector in supporting the global energy transition towards sustainability and reducing the impacts of climate change. This article analyzes the financial performance and strategic decisions of renewable energy companies by evaluating key financial indicators such as liquidity, solvency, profitability, and stability. Furthermore, the study investigates how strategic decisions, including energy portfolio diversification, adoption of innovative technologies, and stakeholder collaborations, influence financial outcomes. The findings highlight that renewable energy companies face significant challenges, including high initial capital investment and regulatory uncertainties. Despite these challenges, financial performance plays a crucial role in facilitating effective strategic decision-making, ultimately enhancing competitiveness. This article also provides actionable recommendations, including cost efficiency measures, supply chain optimization, and leveraging government incentives to support sustainable growth. In conclusion, the alignment of robust financial management with innovative strategies is essential for achieving long-term sustainability and competitiveness in the renewable energy industry.